AC impedance analysis of Bi1-xYxFe0.7Mn0.3O3 multiferroic ceramics - Saha, Sonet Kumar; Ali, Md Ashraf; Hossain, AKM Akther (Journal of Bangladesh Academy of Sciences, 2025)
In this paper, the AC impedance properties of Bi1-xYxFe0.7Mn0.3O3 (BYFMO) ceramics with x values from 0.00 to 0.20 were studied. It was manufactured via solid-state chemistry, and during manufacturing, sintering at temperatures was at 800, 825, and 850°C, and optimal bulk density was at 825°C. X-ray diffraction investigation verified differences in lattice parameters resulting from doping-induced strain and defect structures, suggesting the presence of a rhombohedral phase along with small secondary phases. Field Emission Scanning Electron Microscopy (FESEM) demonstrated a porous microstructure with grain sizes ranging from 1.22 to 1.89 μm. Energy Dispersive X-ray spectroscopy confirmed the elemental composition. The dielectric constant (ε′) demonstrated a frequencydependent reduction, stabilizing beyond 10 kHz. At 100Hz, ε′ rose from 65 to 78 at 100 Hz with increasing Y doping due to a reduction in the quantities of oxygen vacancies. Impedance spectroscopy revealed distinct semicircular patterns in undoped material, indicating grain and grain boundary effects, while doped samples mostly demonstrated grain conduction, elucidating multiferroic electrical transport mechanisms. We have gotten the maximum grain resistance 199.02 MΩ for highest doping at x = 0.20. J. Bangladesh Acad. Sci. 49(2); 271-285: December 2025